"Listen, Hear my Side, Back Me up": What Clients Want from Public Defenders. (25th July 2022) - Pruss, Heather; Sandys, M.; Walsh, S. M.
Abstract: The current study was designed to understand what persons represented by public defenders want from their attorney and how they hope or aspire to interact with their attorney. The results of a thematic analysis of qualitative responses to those inquiries, from 120 people represented by a rural public defender agency, are presented in this article. Though extant literature in this area is scant, the findings here largely echo those prior works: participants articulated a desire for attorneys who effectively communicate, thoroughly investigate, and zealously advocate for them. The data here add nuance, however, to client conceptualizations of those distinct duties, and how clients report they might behave differently with their ideal attorney. Findings also highlight clients' pronounced "resignation" (Casper 1970 ) related to systemic deficiencies in public defense and criminal justice systems more broadly, particularly following case disposition—despite overall satisfaction with their individual attorneys. We conclude by discussing implications for practicing attorneys and possible areas of future research.